2018
DOI: 10.17657/jcr.2018.01.31.5
|View full text |Cite
|
Sign up to set email alerts
|

A Lifestyle Study for Market Segmentation at the Base of Pyramid (BoP) in India

Abstract: This article may be used for research, teaching and private study purposes. Any substantial orsystematic reproduction, redistribution , reselling , loan or sub-licensing, systematic supply ordistribution in any form to anyone is expressly forbidden. The publisher does not give any warranty express or implied or make any representation that the contentswill be complete or accurate or up to date. The accuracy of any instructions, formulae and drug dosesshould be independently verified with primary sources. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The same scenario is for the other typologies of lifestyles. However, it was interesting to identify that contrary to beliefs that BOP consumers prefer only low prices (Ernst et al, 2015;Jagtap et al, 2014;Lee & Kim, 2018;London et al, 2010London et al, , 2014Prahalad, 2005;Sheth, 2011;Viswanathan & Sridharan, 2012), a specific group (innovators and strivers) does not mind paying high prices for brands that represent a different social status. Primarily, technological products are associated with them, confirming that technology for the BOP market is fundamental (Dey & Binsardi, 2016;Irugalbandara & Fernando, 2019;Prahalad, 2005).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The same scenario is for the other typologies of lifestyles. However, it was interesting to identify that contrary to beliefs that BOP consumers prefer only low prices (Ernst et al, 2015;Jagtap et al, 2014;Lee & Kim, 2018;London et al, 2010London et al, , 2014Prahalad, 2005;Sheth, 2011;Viswanathan & Sridharan, 2012), a specific group (innovators and strivers) does not mind paying high prices for brands that represent a different social status. Primarily, technological products are associated with them, confirming that technology for the BOP market is fundamental (Dey & Binsardi, 2016;Irugalbandara & Fernando, 2019;Prahalad, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, Lee and Kim (2018), established that this group of consumers should be evaluated: the level of education, culture, and religion. In this sense, the study revealed a high incidence of these factors, mainly in culture and religion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation